IDENTIFIKASI SISTEM TANAM DAN VARIETAS PADI YANG DIKEMBANGKAN PETANI DI KABUPATEN PEMALANG - Alfina Handayani (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2020)
Increasing rice productivity has been the main priority for the Government of Indonesia to meet people's food needs, however, there are a number of obstacles such as technology adoption. This study aims to explore the condition of farmers' cultivation, especially in terms of planting systems, varieties developed and reasons for selecting varieties in three different land topographic types (low, medium, and high). Sampling was done purposely with a total sample of 45 farmers who cultivate rice. Data collection includes observation and structured interview, data were analyzed descriptively. The results showed that most of the planting system that developed in three types of topography is the ‘tegel’ planting system, other technologies such as “jajar legowo” and system of rice intensification (SRI) have low developed. This is influenced by the new planting system need more skilled labor, more expensive input, and lack of farmers' knowledge. Local rice varieties have declined significantly, dominated by certain superior varieties. The main reason for selecting varieties is due to high productivity and disease resistance. In addition, the accessibility of rice seeds by farmers at the nearest farm shop. This research suggested more intensive mentoring efforts should be done through farmers’ group meetings and improvement of supporting facilities, furthermore the Local Government should improve farmers' affordability of quality seeds.